2018
DOI: 10.3389/fmicb.2018.02712
|View full text |Cite
|
Sign up to set email alerts
|

Afadin Downregulation by Helicobacter pylori Induces Epithelial to Mesenchymal Transition in Gastric Cells

Abstract: Afadin is a cytoplasmic protein of the adherens junctions, which regulates the formation and stabilization of both the adherens and the tight junctions. Aberrant expression of Afadin has been shown in cancer and its loss has been associated with epithelial-to-mesenchymal transition (EMT). EMT is characterized by the change from an epithelial to a mesenchymal phenotype, with modifications on the expression of adhesion molecules and acquisition of a migratory and invasive cell behavior. While it is known that He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…Afadin is a cytoplasmic actin-filament-binding protein responsible for the formation and stabilization of tight and adherens junctions [192][193][194][195]. Marques et al (2018) observed that infection by H. pylori lowered the expression of Afadin protein independently of CagA and VacA in MKN74 and NCI-N87 cell lines [196]. Downregulation of Afadin resulted in dysregulation of tight junctions and adherens junctions, which caused inappropriate cell permeability, stiffness, and impaired transepithelial electrical resistance.…”
Section: Afadin Protein Downregulationmentioning
confidence: 99%
“…Afadin is a cytoplasmic actin-filament-binding protein responsible for the formation and stabilization of tight and adherens junctions [192][193][194][195]. Marques et al (2018) observed that infection by H. pylori lowered the expression of Afadin protein independently of CagA and VacA in MKN74 and NCI-N87 cell lines [196]. Downregulation of Afadin resulted in dysregulation of tight junctions and adherens junctions, which caused inappropriate cell permeability, stiffness, and impaired transepithelial electrical resistance.…”
Section: Afadin Protein Downregulationmentioning
confidence: 99%
“…EMT is a very well-known pathophysiological trans-differentiation process that confers mesenchymal phenotype and properties to epithelial cells. In the gastric context, this EMT is characterized by the loss of epithelial polarity and cellular junctions and the acquisition of a mesenchymal, motile phenotype called the “hummingbird” phenotype [ 7 , 8 , 9 , 10 ]. The overexpression of zinc finger E-box-binding homeobox 1 (ZEB1) and Snail transcription factors and of structural components such as Vimentin, as well as migration and invasion capacities are reminiscent events of the EMT process.…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of Claudin‐18 in these animals led to the activation of multiple signaling pathways involved in cell proliferation and cancer stem cell development, to increased inflammation, and to the appearance of gastric intraepithelial neoplasia and tumorigenesis. In line with these observations, Marques et al showed that H pylori downregulates multiple epithelial cell junction components, including the adherens junction protein Afadin. H pylori downregulates Afadin in vitro and in vivo , and Afadin loss led to the emergence of epithelial‐mesenchymal transition (EMT) and acquisition of an aggressive phenotype in gastric cells .…”
Section: Microbial Agents In Gastric Cancermentioning
confidence: 76%
“…In line with these observations, Marques et al showed that H pylori downregulates multiple epithelial cell junction components, including the adherens junction protein Afadin. H pylori downregulates Afadin in vitro and in vivo , and Afadin loss led to the emergence of epithelial‐mesenchymal transition (EMT) and acquisition of an aggressive phenotype in gastric cells . Accordingly, H pylori promotion of EMT in gastric carcinogenesis by activation of the YAP signaling pathway was also reported …”
Section: Microbial Agents In Gastric Cancermentioning
confidence: 76%